2022
DOI: 10.1136/bmjopen-2021-058494
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of ST-elevation myocardial infarction, age, and sex and the risk of major adverse cardiovascular events among Chinese adults: a secondary analysis of a single-centre prospective cohort

Abstract: ObjectivesThis study aimed to evaluate the interactions of ST-elevation myocardial infarction (STEMI), ageing and sex with respect to the incidence of major adverse cardiovascular events (MACE) among Chinese adults.DesignSecondary analysis of a single-centre prospective cohort.SettingPatients who were admitted to cardiology clinics of the Affiliated Hospital of Jiangsu University due to acute myocardial infarction (MI) from June 2017 to November 2019 were eligible for inclusion in the study. This research only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The close association between age and MACE has been widely confirmed in previous studies. For example, a recent China research demonstrated that elderly ST-elevation myocardial infarction patients showed a 3.3-time increasing incidence of MACE than younger patients [ 23 ]. However, several studies found that the postoperative complications of hip replacement were not related to age, excluding MACE [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The close association between age and MACE has been widely confirmed in previous studies. For example, a recent China research demonstrated that elderly ST-elevation myocardial infarction patients showed a 3.3-time increasing incidence of MACE than younger patients [ 23 ]. However, several studies found that the postoperative complications of hip replacement were not related to age, excluding MACE [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, PCI (Percutaneous coronary intervention) has become a treatment option for AMI through which the patients’ vessels can be dredged in a short time so that the blood flow can be restored. The extent of infarcted myocardium and prognosis are able to get controlled as well [ 5 , 6 ]. In spite of that, complications such as coronary restenosis, ischemia, and malignant ventricular arrhythmias (MVA) after PCI [ 7 ] cannot be completely avoided.…”
Section: Introductionmentioning
confidence: 99%